Geographical heterogeneities and externalities in an epidemiological‐macroeconomic framework. (8th February 2022) - La Torre, Davide; Liuzzi, Danilo; Marsiglio, Simone
Abstract: We analyze the implications of geographical heterogeneities and externalities on health and macroeconomic outcomes by extending a basic epidemiological‐macroeconomic model to a spatial dimension. Because of people's migration and commuting across different regions, a disease may spread also in areas far from those in which the outbreak originally occurs and thus the health status (i.e., disease prevalence) in specific regions may depend on the health status in other regions as well. We show that neglecting the existence of cross‐regional effects may lead to misleading conclusions about the long run outcome not only in single regions but also in the entire economy, suggesting that single regions need to coordinate their efforts to achieve disease eradication. We analyze such a coordination by focusing on a control problem in which the social planner determines globally the level of intervention showing that to achieve eradication it is essential to accompany traditional disease control policies (i.e., prevention and treatment) with regulations limiting people's movements. Focusing on COVID‐19 we present a calibration based on Italian data showing that, because of the infections generated by cross‐regional commuting, even vaccination may not be enough to achieve disease eradication, and limitations on people's movements need to accompany vaccination to preclude COVID‐19 from reaching an endemic state.